2015
DOI: 10.5588/ijtld.15.0257
|View full text |Cite
|
Sign up to set email alerts
|

Late paradoxical lymph node enlargement during and after anti-tuberculosis treatment in non-HIV-infected patients

Abstract: Paradoxical response presents late in about one third of non-HIV-infected patients with lymph node TB who experience a response. Although anti-tuberculosis treatment is commonly prolonged in patients with late paradoxical response, post-treatment lymph node enlargement is more frequent in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
2
11
0
1
Order By: Relevance
“…The reaction occurs in up to 30% of patients [3,6,7] . Yu et al [5] retrospectively reviewed the medical records of 467 non-HIV-infected patients with lymph node TB between 1997 and 2007, and prospectively enrolled patients with newly diagnosed lymph node TB between 2008 and 2013. Eighty-three (18%) patients had PRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction occurs in up to 30% of patients [3,6,7] . Yu et al [5] retrospectively reviewed the medical records of 467 non-HIV-infected patients with lymph node TB between 1997 and 2007, and prospectively enrolled patients with newly diagnosed lymph node TB between 2008 and 2013. Eighty-three (18%) patients had PRs.…”
Section: Discussionmentioning
confidence: 99%
“…Its timing, severity and duration are unpredictable. It may occur anytime during treatment and sometimes even after completing the anti-tuberculosis therapy [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable feature of our case was that PRs had not occurred for 10 years after the completion of anti-TB drugs. A literature review indicated a high propensity of PRs for CNS involvement in comparison to other sites [ 5 , 13 ], and the time of onset of PRs in CNS tuberculosis appears to be longer than the time of onset at other sites [ 1 , 13 ]. These findings may be attributed to frequent brain MRI and/or CT scans conducted for patients with CNS lesions, considering the nature of these lesions, which are likely to result in the manifestation of symptoms leading to disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxical reactions (PRs) to anti-tuberculosis (anti-TB) drugs are defined as the worsening of pre-existing tuberculous lesions or the appearance of new tuberculous lesions in patients whose clinical symptoms initially improved with anti-TB treatment [ 1 6 ]. PRs have been reported in approximately one-third of patients with tuberculous meningitis and typically present within the first few months of the anti-TB treatment [ 4 , 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bei Patienten/-innen mit einer pulmonalen Tuberkulose tritt eine PR selten (< 3 %) auf [49]. Jedoch zeigen einige Studien, dass die Prävalenz der PR bei extrapulmonalen Tuberkulosen im Schnitt nach 2 Monaten bei etwa 18-25 % liegt [50][51][52]. Besonders häufig scheinen Lymphknotentuberkulosen davon betroffen zu sein.…”
Section: Therapieunclassified